2020
DOI: 10.7759/cureus.10830
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Trends in Hospitalization of Attempted Suicide and Self-Inflicted Injury in United States Adults

Abstract: Introduction Suicide is the 10th leading cause of death in the United States (US) and the prevalence continues to increase. It is estimated that there is an average of 25 attempted suicides for every suicide death in the US, and the economic burden of suicide and attempted suicide is high. Identification of those at risk for suicide and attempted suicide can help with early and prompt intervention. Studies in Europe and Asia have shown that there is a relationship between seasonal patterns and suici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Suicide attempts are significant clinical events that lead to a variety of adverse effects, serving as a primary source of distress, morbidity and economic burden 19. Also, those who survive attempted suicide may suffer from consequences such as brain injury and broken bones 42. Previous research has revealed that approximately 18% of individuals who attempt suicide make a second attempt in the following year 43.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suicide attempts are significant clinical events that lead to a variety of adverse effects, serving as a primary source of distress, morbidity and economic burden 19. Also, those who survive attempted suicide may suffer from consequences such as brain injury and broken bones 42. Previous research has revealed that approximately 18% of individuals who attempt suicide make a second attempt in the following year 43.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Also, those who survive attempted suicide may suffer from consequences such as brain injury and broken bones. 42 Previous research has revealed that approximately 18% of individuals who attempt suicide make a second attempt in the following year. 43 In 2013, the total annual estimated economic burden of suicide attempts in the USA exceeded $8 billion.…”
Section: Discussionmentioning
confidence: 99%
“…Em relação ao resultado de maior prevalência nos fins de semanas (sábado e domingo) e nas segundas-feiras, verifica-se que se assemelha a alguns estudos, os quais demonstraram que os registros de óbito por suicídio ocorrem mais nas segundas e nas sextas-feiras, e as tentativas de suicídio e autoflagelação, nos fins de semana (Stark et al, 2010;Onoya et al, 2021). Ainda que alguns estudos apontem que, nos fins de semana, as pessoas estão rodeadas de familiares e amigos, os quais são importantes rede de apoio, evitando teoricamente os pensamentos de autoflagelação, não há consenso na literatura sobre a variação da incidência ao longo dos dias da semana (Oladunjoye et al, 2020;Meydroidt et al, 2020).…”
Section: Discussionunclassified
“…Risk factors for suicidal behavior in bipolar disorder include depression, agitation, impulsivity, comorbid alcohol or substance abuse, prior suicidal acts, recent discharge from a psychiatric hospital, along with genetic, demographic, socioeconomic and cultural factors, and stressful life events (Pompili et al 2013 ; Shaffer 2015 ; Tondo et al 2021 ; Bachmann 2018 ; Plans et al 2019 ; Tidemalm et al 2014 ). Additionally, international epidemiology studies of the general population spanning several decades report seasonality in suicide attempts and deaths with a peak in spring or summer (Galvão et al 2018 ; Woo et al 2012 ; Su et al 2020 ; Postolache et al 2010 ; Oladunjoye et al 2020 ; Christodoulou et al 2012 ; Coimbra et al 2016 ; Petridou et al 2002 ).…”
Section: Introductionmentioning
confidence: 99%